Effects of manual therapy and TENSI massage technique on facial aging - Silva Ventura, Danielle Bastos; Meyer, Patrícia Froes; da Silva, Rodrigo Marcel Valentim; Carreiro, Eneida de Morais; Maia, Rafaella Rêgo; Diniz, Laura Vieira Pires; Farias, Stephany Luanna Queiroga (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Skin aging can be delayed through therapeutic resources. In manual therapy, myofascial stretching has been used to mobilize the structures of the skin, fasciae and muscles in order to reorganize the collagen, improving the appearance of the skin. Objective: Investigate the effects of TENSI massage technique, associated or not with firming cream, on skin aging. Methods: The sample consisted of 27 volunteers, over the age of 40, who had static and/or dynamic wrinkles caused by facial skin aging. Th e evaluation was performed using the facial evaluation protocol (FEP), photos, morphological analysis of the face by the Dolphin Imaging Software and questionnaires. The volunteers were divided into two subgroups: G1 - Manual therapy with 12 volunteers and G2 - Manual therapy and cosmetics with 15 volunteers. The treatment was carried out in three cycles. Each cycle corresponded to 5 weeks, with two treatment sessions per week for the first 3 weeks and one session per week for the 4th and 5th weeks. The protocol start ed with face cleaning, followed by cutaneous myostretching. Only the G2 used the firming cream together with the therapy. Results: The software analysis showed changes in both groups, with improvement in the paralateronasal line, in the mandibular projection and in the nasolabial angle, however, these were better perceived in the volunteers of the G2. No adverse reactions were reported and few volunteers observed hyperemia at the skin. The firmness of the skin was reported as “Much firmer” in the vast majority of volunteers, as well as the classification in “Excellent treatment”. Conclusion: The myofascial stretch caused by the TENSI Method proved to be effective in improving skin aging, however, its results are even more satisfactory when adding firming cosmetics